Trends in halogen-containing molecules measured by the Atmospheric Chemistry Experiment (ACE) satellite. (November 2019) - Steffen, Johnathan; Bernath, Peter F.; Boone, Chris D.
Highlights: ACE has measured VMRs of 16 halogen-containing molecules for 2004–2018. VMR trends and altitude-latitude distributions are calculated. Trends for CCl4, CFCs, and HCl indicate the success of the Montreal Protocol. VMRs of CF4, SF6, HCFC-22, HCFC-141b, HCFC-142b and HF continue to increase. CF4, CFC-113, HCFC-141b and HFC-142b altitude-latitude distributions show artifacts. Abstract: The Montreal Protocol has banned the production of long-lived halogen-containing molecules such as chlorofluorocarbons (CFCs) that are responsible for the widespread destruction of stratospheric ozone. Sixteen halogen-containing trace gases (CCl4, CF4, CFC-11, CFC-12, CFC-113, CH3 Cl, ClONO2, COCl2, COClF, COF2, HCFC-22, HCFC-141b, HCFC-142b, HCl, HF, SF6 ) are observed globally by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) which measures atmospheric spectra via solar occultation from low-Earth orbit. The ACE satellite was launched in August 2003 and continues to operate with minimal degradation to this day. ACE is uniquely able to provide global long term trends of the concentrations of many atmospheric constituents. In this work we present time series trends and altitude-latitude distributions of halogen-containing trace gases. For 12 molecules the altitude-latitude distributions are reliable, but for CF4, CFC-113, HCFC-141b and HCFC-142b the distributions are anomalous likely because of spectroscopic interference in the retrieval. These 16 species can be categorized as source gases such as CFCs emitted at the surface and product gases such as HCl, HF and ClONO2 that are formed by chemical reactions from the source gases. Many of these substances deplete stratospheric ozone and are potent greenhouse gases that contribute to climate change.